The Influence of Lightning and Grounding Conditions On Flashover Events in a 150kV Transmission Line - Novizon Novizon; Rusvaira Qatrunnada; Mardini Hasanah; Heru Dibyo Laksono (Andalasian International Journal of Applied Science, Engineering and Technology, 2024)
Effect of lightning parameters and grounding system impedance on transient overvoltage that occurs in 150 kV overhead transmission lines during lightning using ATP-EMTP modeling. The induced overvoltage that jumps across the insulator is calculated for further analysis. Various parameters that directly influence directly influence the backflashover phenomenon,, such as the effect of lightning strike amplitude, time of rise (front) and decay (tail) of lightning impulses, foot grounding system, and ground resistivity,, are discussed in more detail. Surge arresters are used in this study to overcome the overvoltage that can cause backflashover. The performance of the transmission system after using a surge arrester is investigated at the time of a lightning strike. The results indicate that the parameters of the advance time and the lightning current amplitude greatly affect the overvoltage magnitude voltage. Other parameters have little effect on the overvoltage in the transmission line.